1997
DOI: 10.1055/s-0038-1655985
|View full text |Cite
|
Sign up to set email alerts
|

Low Prevalence of Factor V:Q506 in 41 Patients with Isolated Pulmonary Embolism

Abstract: SummaryIn 70-80% of cases, pulmonary embolism is the consequence of lower extremity deep vein thrombosis. It has been demonstrated that the most common coagulation defect predisposing to venous thrombosis, resistance to activated protein C (APC), is not associated with an increased risk for pulmonary embolism, but the evidence was based on a functional assay to diagnose APC resistance and no information about concomitant deep vein thrombosis was provided. The aim of our study was to evaluate the prevalence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
63
3

Year Published

2000
2000
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(78 citation statements)
references
References 14 publications
12
63
3
Order By: Relevance
“…Our study confirms and further substantiates most of the earlier findings (Desmarais et al, 1996;Manten et al, 1996;Baglin et al, 1997;Martinelli et al, 1997;Turkstra et al, 1999), indicating that the prevalence of APC resistance or factor V Leiden mutation in patients with isolated PE is about half the prevalence of that in patients with DVT (Table III). The prevalence of factor V Leiden in PE in our study is well within the range observed in these studies.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our study confirms and further substantiates most of the earlier findings (Desmarais et al, 1996;Manten et al, 1996;Baglin et al, 1997;Martinelli et al, 1997;Turkstra et al, 1999), indicating that the prevalence of APC resistance or factor V Leiden mutation in patients with isolated PE is about half the prevalence of that in patients with DVT (Table III). The prevalence of factor V Leiden in PE in our study is well within the range observed in these studies.…”
Section: Discussionsupporting
confidence: 92%
“…For example, the mean age of patients with primary PE (71 years) in the present study is much higher than in the study of Manten et al (1996) (45 years) and in the study of Martinelli et al (1997) (41 years). However, even if there are differences in methodologies and populations, one fact constantly emerges: the prevalence of factor V Leiden is more than doubled in DVT patients over isolated PE patients.…”
Section: Discussioncontrasting
confidence: 78%
See 1 more Smart Citation
“…We observed the factor V Leiden paradox which has been described elsewhere [4][5][6][7][8][9][10] in our population as well. As to the suggestion of different clot-structure in persons carrying factor V Leiden, which could be supposed to be due to activated protein C resistance, one would expect to also find it in other thrombophilic defects influencing activated protein C, like protein S deficiency for example.…”
Section: Resultssupporting
confidence: 81%
“…4 This differential effect is known as the "factor V Leiden paradox" 5 and has been reported repeatedly. [6][7][8][9][10] A pathophysiological mechanism that can explain the factor V Leiden paradox is not at hand. The hypothesis that presence of factor V Leiden would often lead to fatal pulmonary embolism, resulting in a lower number of factor V Leiden carriers among those surviving pulmonary embolism and thereby explaining this paradox, has been rejected as autopsy studies have shown that among patients with fatal pulmonary embolism, the proportion of subjects with factor V Leiden did not differ from that in pulmonary embolism survivors or from the general population.…”
Section: Introductionmentioning
confidence: 99%